PEMBUATAN SIMULASI PERCOBAAN PADA MATERI GELOMBANG DALAM PEMBELAJARAN FISIKA KELAS XII SMA - Ayu Lusiyana (Universitas Negeri Padang, 2013)
Experiments simulation product made by using Adobe Flash CS 3 Professional software in order that students can understanding of physics concept. This product is intended to analyze the phenomena and symptom that occur in a real experiment. The aims of this research is to produce a valid, practical and effective of an experiments simulation. This research including Research and Development (R & D) type and the instrument of research used pieces of the validation by experts, teachers and student response sheets as sheet practicalities, and learning outcomes assessment sheets. Based on the data analysis obtained average value product validation is 4.05 which suggests that experiments simulation have high validity. The average value of the result data analysis of practicalities is 85,5% meaning attempts simulations are practice. The test results obtained from the sheet effectiveness of student learning outcomes before and after the study showed an increase in student learning outcomes, experiments simulation effectively used in teaching physics in Senior High School grade XII. Keywords – Experiment Simulation, Laboratory, Physics Learning